2006
DOI: 10.1111/j.1479-8077.2006.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Cranial and peripheral neuropathy in rheumatoid arthritis with special emphasis to II, V, VII, VIII and XI cranial nerves

Abstract: Background:  Cranial neuropathy in rheumatoid arthritis (RA) is relatively rare compared to the frequently reported peripheral neuropathy. Methods:  We investigated the occurrence of subclinical cranial and peripheral nerve involvement in 55 patients with RA. Results:  Patients had a mean age of 43.1 years and a mean duration of illness of 6.4 years. All patients presented with electrophysiological findings suggestive of peripheral neuropathy. In addition, 69.1% of them had entrapment neuropathies, in which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…The current study found no correlation between age and peripheral neuropathy and it is similar to some other studies,[8] but certain studies[4514] have found a relationship between the two. Albani et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study found no correlation between age and peripheral neuropathy and it is similar to some other studies,[8] but certain studies[4514] have found a relationship between the two. Albani et al .…”
Section: Discussionsupporting
confidence: 92%
“…The finding is similar to studies by Albani et al . [13] but certain other studies[614] found sensorimotor neuropathy to be the most frequent subtype. A very important benefit of electrophysiological study in patients with RA is early detection of entrapment neuropathy (detected in 4% of our patients) as it is amenable to treatment.…”
Section: Discussionmentioning
confidence: 96%
“…have found a positive association between presence of neuropathy and disease duration. [324] Our study also showed a similar result. A significant association was found between inflammatory markers of disease activity (ESR, CRP) and peripheral neuropathy in our study.…”
Section: Discussionsupporting
confidence: 86%
“…In SS studies, CNS manifestations range between 9 and 44% and PNS ranged between 24 and 68%, which agree with previous studies [ 36 ]. In this review, the frequency of PNS (mononeuritis) in RA patients is 18% lower as compared to other study, while for entrapment neuropathy (6% in our patients) it varies from 4% to 54.6% [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 48%